Reassessment of Islamic astronomical sciences - Shuriye, Abdi Omar (INSInet Publications, 2011)
This paper attempts to reevaluate Muslim input to astronomy. Underling the efforts and the contributions of Al–Biruni and Al–Battani to astronomy is the core concern of this paper. Astronomy is one of the sciences that have existed since the dawn of recorded civilization. It has been called the queen of sciences and it incorporates many disciplines such as physics, optics in particular, and mathematics, as well as celestial mechanics. Reassessing the contributions of Muslim scholars and Qur’anic views on astronomy is an urgent call in a time when knowledge is claimed by one civilization, the Western civilization.